Cost-effectiveness of enhanced syphilis screening among HIV-positive men who have sex with men: a microsimulation model. - Ashleigh R Tuite; Ann N Burchell; David N Fisman (PLoS ONE, 2014)
Syphilis co-infection risk has increased substantially among HIV-infected men who have sex with men (MSM). Frequent screening for syphilis and treatment of men who test positive might be a practical means of controlling the risk of infection and disease sequelae in this population.We evaluated the cost-effectiveness of strategies that increased the frequency and population coverage of syphilis screening in HIV-infected MSM receiving HIV care, relative to current standard of care.We developed a state-transition microsimulation model of syphilis natural history and medical care in HIV-infected MSM receiving care for HIV. We performed Monte Carlo simulations using input data derived from a large observational cohort in Ontario, Canada, and from published biomedical literature. Simulations compared usual care (57% of the population screened annually) to different combinations of more frequent (3- or 6-monthly) screening and higher coverage (100% screened). We estimated expected disease-specific outcomes, quality-adjusted survival, costs, and cost-effectiveness associated with each strategy from the perspective of a public health care payer.Usual care was more costly and less effective than strategies with more frequent or higher coverage screening. Higher coverage strategies (with screening frequency of 3 or 6 months) were expected to be cost-effective based on usually cited willingness-to-pay thresholds. These findings were robust in the face of probabilistic sensitivity analyses, alternate cost-effectiveness thresholds, and alternate assumptions about duration of risk, program characteristics, and management of underlying HIV.We project that higher coverage and more frequent syphilis screening of HIV-infected MSM would be a highly cost-effective health intervention, with many potentially viable screening strategies projected to both save costs and improve health when compared to usual care. The baseline requirement for regular blood testing in this group (i.e., for viral load monitoring) makes intensification of syphilis screening appear readily practicable.